Introduction to decimal fractions. - Harper & Row, Publishers (White Plains, N.Y. : Center for Humanities, 1979)
Topics covered include place value, writing decimals as fractions, addition, subtraction, multiplication of decimals, powers of 10, and rounding off.
"The skills group."
Also issued with sound accompaniment on disc.
Keywords: Decimal fractions